Presidents in the Movies
X, 198 p.
Keywords: Cinematic depictions of real U.S. presidents from Abraham Lincoln to George W. Bush explore how Hollywood movies represent American history and politics on screen. Morgan and his contributors show how films blend myth and reality to present a positive message about presidents as the epitome of America's values and idealism until unpopular foreign wars in Vietnam and Iraq led to a darker portrayal of the imperial presidency, operated by Richard Nixon and Bush 43. This exciting new collection further considers how Hollywood has continually reinterpreted historically significant presidents, notably Abraham Lincoln, Theodore Roosevelt, and Franklin D. Roosevelt, to fit the times in which movies about them were made.